Ionic liquids uncoiled : critical expert overviews - Plechkova, Natalia V.; Seddon, Kenneth R., 1950- (Hoboken, N.J. : John Wiley & Sons, 2013)
'The book presents articles on topics at the forefront of ionic liquids research range from applied to theoretical, from synthetic to analytical, from biotechnology to electrochemistry, from process engineering to nanotechnology'--
Includes bibliographical references and index.
Keywords: Ionic solutions; Ionic structure